Sustainable development strategies for improving the efficiency and safety of a highway in Iraq - Had, Ahmed; Ghazali, Farid Ezanee Mohamed; Jrew, Basim; Hassoon, Ali (Edelweiss Applied Science and Technology, 2025)
The performance of two-lane, two-way highways in Iraq, especially in rural areas, is often hindered by high traffic volumes, inadequate infrastructure, and safety concerns. This research focuses on evaluating and improving the performance of the highway connecting Salah al-Din Governorate to Kirkuk Governorate, which faces significant congestion and safety challenges. Using the Highway Capacity Software (HCS 2024) and the Highway Capacity Manual (HCM 7th edition), the study aims to assess the current and short-term future conditions of the highway, particularly in terms of traffic flow and service levels. The study discusses prominent factors influencing the highway's operational performance, including traffic composition, geometric design, and safety considerations, and proposes specific improvements for service quality enhancement and congestion relief. Proposed measures include lane widening and speed limit adjustments. The research addresses the creation of predictive models to estimate future traffic volume and levels of service, thereby providing valuable information on possible improvements that would make highways both safer and more efficient. The research plays a critical role in informing future planning and highway infrastructure development in Iraq, especially in areas with similar issues.